Outcomes, Opportunity and Development : Why Unequal Opportunities and Not Outcomes Hinder Economic Development - Molina, Ezequiel; Narayan, Ambar; Saavedra-Chanduvi, Jaime (World Bank, Washington, DC, 2015)
This paper studies the relationship between inequality of opportunity and development outcomes in a cross-country setting. Scholars have long debated the impact of inequality on growth, development, and the quality of institutions in a society. The empirical relationships are however confounded by the notion that "inequality" can be seen as a composite of inequality arising from differences in effort and ability, which would tend to encourage competition and productivity, and inequality attributable to unequal opportunities, particularly in terms of access to basic goods and services, which might translate to wasted human potential and lower levels of development. The analysis in this paper applies a measure of educational opportunities that incorporates inequality between "types" or circumstance groups. Theories from economic history are used to instrument for this type of inequality in a large cross-country dataset. The results seem to confirm the hypothesis that this measure of inequality of opportunity is a better fit for structural inequality than the Gini index of income. The results suggest that inequality of endowments at the outset of history led to unequal educational opportunities, which in turn affected development outcomes such as institutional quality, infant mortality, and economic growth. The findings are robust to several checks on the instrumental variable specification.